Improving the performance of dairy cattle with a xylanase-rich exogenous enzyme preparation - Martins, R. M. (2016)
The objective of this experiment was to examine effects of adding 2 exogenous fibrolytic enzymes (EFE) to the total mixed ration (TMR) on the performance of lactating dairy cows (experiment 1) and the kinetics of ruminal degradation of the diet (experiment 2). Twelve EFE had been screened in a series of in vitro assays that identified the most potent EFE and their optimal doses for increasing the digestibility of bermudagrass. In experiment 1, 66 Holstein cows (21 ± 5 d in milk) were grouped by previous milk production and parity (45 multiparous and 21 primiparous) and assigned randomly to 1 of the following 3 treatments: (1) control (CON, untreated), (2) Xylanase Plus [2A, 1 mL/kg of TMR dry matter (DM); Dyadic International, Jupiter, FL], and (3) a 75:25 (vol/vol) mixture of Cellulase Plus and Xylanase Plus EFE (3A, 3.4 mL/kg of TMR DM; Dyadic International). The EFE were sprayed twice daily onto a TMR (10% bermudagrass silage, 35% corn silage, 5% alfalfa-orchardgrass hay mixture, and 50% concentrates; DM basis) and fed for a 14-d training and covariate period and a 70-d measurement period. Experiment 2 aimed to examine the in situ DM ruminal degradability and ruminal fermentation measurements of the diets fed in experiment 1. Three ruminally fistulated lactating Holstein cows were assigned to the diets. The experiment had a 3 × 3 Latin square design with 23-d periods. In experiment 1, application of 2A increased intakes (kg/d) of DM (23.5 vs. 22.6), organic matter (21.9 vs. 20.9), and crude protein (3.9 vs. 3.7) and tended to increase yields (kg/d) of fat-corrected milk (41.8 vs. 40.7) and milk fat (1.48 vs. 1.44). In particular, 2A increased milk yield (kg/d) during wk 3 (41.2 vs. 39.8, tendency), 6 (41.9 vs. 40.1), and 7 (42.1 vs. 40.4), whereas 3A increased milk yield (kg/d) dur- ing wk 6 (41.5 vs. 40.1, tendency), 8 (41.8 vs. 40.0), and 9 (40.9 vs. 39.5, tendency). In experiment 2, EFE treatment did not affect ruminal DM degradation kinetics or ruminal pH, ammonia-N, and volatile fatty acid concentration. Application of 2A to the bermudagrassbased TMR increased DM intake and milk production, implying that this EFE could be used to increase the performance of lactating dairy cows fed diets containing up to 10% bermudagrass.